Proyecto de inversión para la creación de una empresa recicladora de gases refrigerantes en el servicio de mantenimiento y reparación de equipos de refrigeración y aires acondicionados en Buenaventura-Valle del Cauca (2013)
The development and structure of the research study is based on existing needs and behavior of the service sector in the district of Buenaventura, valle del cauca, in order to achieve to know the perspectives of customers and the degree of satisfaction regarding the repair service and maintenance of addition to assessing the acceptability and feasibility to use special techniques for the recovery of refrigerants helping the environmental impact the study defines the problem and identifies the need in the market, the technical, administrative and financial, taking into account the objectives and rationale, the frame of reference, the definition, the expected results, financial and environmental guidelines, the schedule and costs of the investigation, in accordance with a preset working methodology, the main objective of the research is to analyze the existing market to break into Buenaventura, valle del cauca with a refrigerant gas recycling company in the service and maintenance repair operations in refrigeration equipment fitted with machinery technology and personnel competent to provide in service to customers and therefore know the market study and the behavior of the technical service sector in the district of Buenaventura – Valle del Cauca.